Pengujian Konsistensi Pengukuran Kinerja Reksa Dana Campuran Dengan Menggunakan Methode Sharpe, Treynor dan Jensen - , Jekson B. Simanjuntak ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to evaluate mix mutual fund which was listing in Bursa Efek Jakarta (Jakarta Stock Exchange) during period of January 2006 until December 2009 and also to see consistancy of relationship between measurement method for mutual fundâs performance which are Sharpe, Treynor and Jensen. This research involved 42 samples which had fulfilled criteria. The criteria is the samples must be listed in Jakarta Stock Exchange during the research period. To rank mix mutual fundâs performances, this research used Sharpe, Treynor dan Jensen methods. To solve the problem, this research used non parametrik correlation- Kendallâs Tau_b. The result showed that the best performance mix mutual fund consistantly during January 2006 until December 2009 are Danamas Fleksi and Fortis Equitra.. the worst performance mix mutual fund consistantly during January 2006 until December 2009 is Schroder Dana Terpadu. The result also showed that there is cconsistancy between three variables, Sharpe, Treynor and Jensen.